FENOMENA BUDAYA KONSUMERISME PRAKTIS DALAM PERSPEKTF DESAIN PRODUK. (FURNITURE - Boike Janus Anshory (Universitas Trisakti, 2017)
AbstractIn the modern era and the development of technology today, there is a tendency of human activity that are faced with the practical cultural phenomenon in the sense of many human activities are permitted to make ends meet. Human activity will be smooth if it is complemented by the completeness of the activities referred to as